Sustainability Report Disclosure Reviewed with Good Corporate Governance Mechanism - Pangestu, Ilham Ferdinan; Zulfikar, Z (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The intention of the investigation is to investigate how an effective institution’s management system influences sustainability report disclosure. Methodology: This study employs both quantitative and non-probability (purposeful) testing methods. This research looked at 81 samples that satisfied the criteria for firms included in the LQ-45 Index. SPS program used statistical methods to examine the data. Results: This study discovered that concerns raised by the Board of Commissioners and the Board of Directors have a significant impact on the release of sustainability reports. The study's findings suggest that efficient cooperation between the members of the Board of Commissioners (operational supervisors) and the the Council of Directors (operational staff) allows firms to widely disseminate sustainability report information. Effective monitoring and policy formulation pushes organisations to prioritise execution, inventiveness, and value. This study is founded on the stakeholder hypothesis, which claims that the Boards of Commissioners and Directors have a favorable relationship with sustainability disclosure. Value: This analysis makes use of the most recent GRI indicators, those from GRI Index 2021.